Neuropharmacological Effects of the Dichloromethane Extract from the Stems of Argemone ochroleuca Sweet (Papaveraceae) and Its Active Compound Dihydrosanguinarine - Eunice Yáñez-Barrientos; Juan Carlos Barragan-Galvez; Sergio Hidalgo-Figueroa; Alfonso Reyes-Luna; Maria L. Gonzalez-Rivera; David Cruz Cruz; Mario Alberto Isiordia-Espinoza; Martha Alicia Deveze-Álvarez; Clarisa Villegas Gómez; Angel Josabad Alonso-Castro (MDPI AG, 2023)
Argemone ochroleuca Sweet (Papaveraceae) is used in folk medicine as a sedative and hypnotic agent. This study aimed to evaluate the anxiolytic-like, sedative, antidepressant-like, and anticonvulsant activities of a dichloromethane extract of A. ochroleuca stems (AOE), chemically standardized using gas chromatography-mass spectrometry (GC-MS), and its active compound dihydrosanguinarine (DHS). The anxiolytic-like, sedative, antidepressant-like, and anticonvulsant activities of the AOE (0.1-50 mg/kg p.o.) and DHS (0.1-10 mg/kg p.o.) were evaluated using murine models. A possible mechanism for the neurological actions induced by the AOE or DHS was assessed using inhibitors of neurotransmission pathways and molecular docking. Effective dose 50 (ED50) values were calculated by a linear regression analysis. The AOE showed anxiolytic-like activity in the cylinder exploratory test (ED50 = 33 mg/kg), and antidepressant-like effects in the forced swimming test (ED50 = 3 mg/kg) and the tail suspension test (ED50 = 23 mg/kg), whereas DHS showed anxiolytic-like activity (ED50 = 2 mg/kg) in the hole board test. The AOE (1-50 mg/kg) showed no locomotive affectations or sedation in mice. A docking study revealed the affinity of DHS for α2-adrenoreceptors and GABAA receptors. The anxiolytic-like and anticonvulsant effects of the AOE are due to GABAergic participation, whereas the antidepressant-like effects of the AOE are due to the noradrenergic system. The noradrenergic and GABAergic systems are involved in the anxiolytic-like actions of DHS.